PENGEMBANGAN TIPOLOGI INOVASI PELAYANAN PUBLIK - Wisber Wiryanto (Inovasi, 2021)
There are various population administration (adminduk) services, in various provinces, districts and cities in Indonesia. However, the quality of service varies, because geographical conditions, local and global problems, as well as the ability to implement policies it faces varies. Then, it is necessary to have an innovation that has a typology as needed to improve service quality. Therefore, the research was conducted about development of public service innovation typology. This paper attempt to addres a key research question, how typology of adminduk service innovation? The aim of this research was to identify the typology of adminduk service innovation. The research method uses literature review by using relevant references, documents and data. The sample of this research in total 23 agencies that carry out adminduk service innovation. The sample was taken using accidental sampling technique, as the data source. Qualitative descriptive data analysis was used to identify a typology of adminduk service innovation. The research was conducted in the first semester of 2020. The results of this study shown, typology of adminduk public service innovation, consisting of 8 types of innovation, namely: innovation of input, proces, output, system, concept, administration, technology, governance. The relevant population and civil registration agency need to identify a typology of innovation as needed before the process of initiation or replication of innovation is carried out in order to reach efficient and effective results.